Innovation for Inclusive value-chain development: Highlights - Horton, Douglas; Donovan, Jason; Devaux, André; Torero, Máximo (International Food Policy Research Institute, 2016)
Despite increasing use of innovation-system and value-chain approaches to promote rural income growth, poverty reduction, and greater gender equity, there is little systematic knowledge about how to operationalize valuechain approaches in different contexts and how best to evaluate innovation and value-chain development. In this book, we bring together 14 papers (chapters)-of which 12 were previously published as journal articles-that present results of recent work associated with CGIAR and its partners in Africa, Asia, and Latin America. The papers assess the opportunities emerging from new and expanding markets for agricultural produce and identify challenges to smallholder participation in these markets and the resulting benefits. They illustrate how interventions have fostered agricultural innovation and inclusive value-chain development, and the extent of their impacts. Methods for evaluating complex interventions that involve innovation and value-chain development are presented, along with empirical results of evaluation studies. From an analysis of the cases presented, we discuss emerging issues and policy implications, and identify knowledge gaps and priorities for future applied research and evaluation.